Composite membrane of sulfonated polybenzimidazole and sulfonated graphene oxide for potential application in microbial fuel cell. Issue 1 (February 2021) - Mondal, Sudipta; Papiya, Farhan; Ash, Saumendra Nath; Kundu, Patit Paban
Abstract: In this study, various composite membranes consisting of sulfonated polybenzimidazole (SPBI) and varying amounts of sulfonated graphene oxide (SGO) were synthesized with an aim for their potential application in microbial fuel cells (MFCs). SPBI is prepared from PBI by reacting it with 2-chloro ethane sulfonic acid and the structure of SPBI is confirmed by proton nuclear magnetic resonance spectroscopy, Fourier transform infrared spectroscopy and X ̶ ray diffraction analysis. The proton conductivity, ion exchange capacity (IEC) and tensile modulus of the composites increase with the higher content of SGO in SPBI. Membranes with 3% and 5% SGO content exhibit superior IECs (0.912 and 1.001 meqg ̶ 1 ) and proton conductivity (0.016 and 0.018 S cm –1 ) at room temperature. The enhancement of these properties is owing to the increasing content of ̶ SO3 H groups in the SGO/SPBI composite, increasing the channel availability for the transport of protons. Amongst the three composite membranes (1%, 3% and 5% of SGO in SPBI), the 3% SGO/SPBI composite membrane showed the highest open-circuit voltage of ~ 669 ± 18 mV, when applied in an MFC. Furthermore, the application of the nanocomposite membrane (3% SGO/SBI) in MFC showed a power density of 472.46 mWm ̶ 2 at a potential value of 0.234 V which was equivalent to 98.16% of Nafion membrane (481.3 mWm ̶ 2 ). Thus, the newly developed SGO/SPBI composite membranes have the potential for application in MFC. Graphical Abstract: ga1 Highlights: Sulfonated graphene oxide emerged as an effective filler for a composite membrane for application in microbial fuel cells. SGO incorporated sulfonated polybenzimidazole polymer electrolyte membranes are developed for application in MFCs. In comparison to the SPBI membrane, higher proton conductivity and ion exchange capacity was observed. 3 wt% SGO/SPBI composite membrane was found to be superior membrane properties and membrane efficiency in MFC. MFC with 3 wt% SPBI/SGO composite membrane generates the highest power density of 472.46 mWm –2 .